Damma Silalahi and the Representation of Simalungun Culture in Contemporary Pop Music - Sihombing, Nova Indriana; Tarigan, Kumalo (Gondang: Jurnal Seni dan Budaya, 2025)
This study examines Simalungun pop songs by Damma Silalahi, which have significantly influenced the development of popular music in Simalungun society. The main objectives of this study are to analyze the musical structure, uncover the textual meaning, and evaluate the social function of ten purposively selected songs. The study uses a qualitative approach with a descriptive-analytical method. The analysis of musical structure is conducted using William P. Malm's theory of scale, melodic contour, and melodic formula, while the analysis of the meaning of the lyrics is based on semiotic theory and the theory of meaning in semantics and pragmatics. The main findings show that Damma Silalahi's songs combine modern style with traditional Simalungun musical roots. The lyrics express themes of love, social criticism, religiosity, and respect for parents. The social functions of these songs include expressive, educational, and recreational functions. Damma's works not only represent the dynamics of Simalungun culture but also reconstruct cultural identity within a contemporary framework. This study contributes new understanding of the transformation of regional music in a society experiencing modernization and globalization.